The integration of single-familiy housing in urban design: towards Mixed Development in Huesca (Ciudades, 2025)
Urban design in the second half of the 20th century has developed according to social, cultural and economic factors and demands. Thus, mixed development arose in response to a wide demand for typological variety, where the single-family housing would be one of these typologies to be integrated and combined with others in the form of collective housing. The process experienced in Huesca is analysed, starting with a clear typological separation, followed by actions with the addition of areasaccording typologies, and ending with projects that achieve the maximum integration of single-familyhousing with a true mixture within the urban design.
Keywords: Planning; Urban design; Mixed development; Single-family house; Huesca; Spain